THE SIGNIFICANCE OF INTERNAL MOTIVATION IN LANGUAGE LEARNING PROCEDURE AND OVERALL PSYCHOLOGICAL WELL-BEING OF STUDENTS - Mirsalikhova Robiya Timurovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract Internal motivation plays a pivotal role in the process of language acquisition and proficiency development. This abstract aims to explore the fundamental significance of internal motivation in language learning, shedding light on its transformative influence on learners' attitudes, engagement, and ultimately, their linguistic competence. By delving into the underlying principles of internal motivation and its impact on language acquisition, this abstract offers a comprehensive understanding of the crucial role it plays in shaping successful language learning experiences.